Rock paper scissors [large type] - Feeney, Alice (Thorndike Press, a part of Gale a Cengage company, 2021)
"Rock Paper Scissors is the latest exciting domestic thriller from the queen of the killer twist, New York Times bestselling author Alice Feeney. Think you know the person you married? Think again ... Things have been wrong with Mr and Mrs Wright for a long time. When Adam and Amelia win a weekend away to Scotland, it might be just what their marriage needs. Self-confessed workaholic and screenwriter Adam Wright has lived with face blindness his whole life. He can't recognize friends or family, or even his own wife. Every anniversary the couple exchange traditional gifts--paper, cotton, pottery, tin--and each year Adam's wife writes him a letter that she never lets him read. Until now. They both know this weekend will make or break their marriage, but they didn't randomly win this trip. One of them is lying, and someone doesn't want them to live happily ever after. Ten years of marriage. Ten years of secrets. And an anniversary they will never forget"--|cProvided by publisher